Systematic review and network meta-analysis comparing clinical outcomes and effectiveness of surgical treatments for haemorrhoids. Issue 13 (30th September 2015) - Simillis, C; Thoukididou, S N; Slesser, A A P; Rasheed, S; Tan, E; Tekkis, P P
Abstract: Background: The aim was to compare the clinical outcomes and effectiveness of surgical treatments for haemorrhoids. Methods: Randomized clinical trials were identified by means of a systematic review. A Bayesian network meta-analysis was performed using the Markov chain Monte Carlo method in WinBUGS. Results: Ninety-eight trials were included with 7827 participants and 11 surgical treatments for grade III and IV haemorrhoids. Open, closed and radiofrequency haemorrhoidectomies resulted in significantly more postoperative complications than transanal haemorrhoidal dearterialization (THD), LigaSure™ and Harmonic® haemorrhoidectomies. THD had significantly less postoperative bleeding than open and stapled procedures, and resulted in significantly fewer emergency reoperations than open, closed, stapled and LigaSure™ haemorrhoidectomies. Open and closed haemorrhoidectomies resulted in more pain on postoperative day 1 than stapled, THD, LigaSure™ and Harmonic® procedures. After stapled, LigaSure™ and Harmonic® haemorrhoidectomies patients resumed normal daily activities earlier than after open and closed procedures. THD provided the earliest time to first bowel movement. The stapled and THD groups had significantly higher haemorrhoid recurrence rates than the open, closed and LigaSure™ groups. Recurrence of haemorrhoidal symptoms was more common after stapled haemorrhoidectomy than after open and LigaSure™ operations. No significant difference was identified between treatments for anal stenosis, incontinence and perianal skin tags. Conclusion: Open and closed haemorrhoidectomies resulted in more postoperative complications and slower recovery, but fewer haemorrhoid recurrences. THD and stapled haemorrhoidectomies were associated with decreased postoperative pain and faster recovery, but higher recurrence rates. The advantages and disadvantages of each surgical treatment should be discussed with the patient before surgery to allow an informed decision to be made. Abstract : Effective treatment for haemorrhoids?